2008
DOI: 10.1016/j.entcs.2008.04.099
|View full text |Cite
|
Sign up to set email alerts
|

Algebraic Structure of Web Services

Abstract: Web Services and Service-Oriented Architecture in general are promising concepts to overcome difficulties such as heterogeneity, scalability, etc. In this paper we present an algebraic structure of Web Services which assist users in Web Service composition and formal description of their services. Using relation algebra, tests and iteration offer the possibility of an automatic composition of Web Services based on a specified goal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Using relation algebra, tests and iterations offer the possibility of an automatic composition of Web services based on a specified goal. However, the syntax, and semantics used in 10 do not seem intuitive for modeling and verification process.…”
Section: Related Workmentioning
confidence: 97%
See 1 more Smart Citation
“…Using relation algebra, tests and iterations offer the possibility of an automatic composition of Web services based on a specified goal. However, the syntax, and semantics used in 10 do not seem intuitive for modeling and verification process.…”
Section: Related Workmentioning
confidence: 97%
“…In order to satisfy such requirements, we propose a Web service algebra that can model and verify Web services in a much more efficient manner. Though researchers have proposed several algebras focused on Web services 8,9,10 , these do not give emphasis on recursive nature of service composition and also do not explore on the verification aspect of composition. Therefore, we emphasize that a Web services algebra should have its own basic computational model on recursive composition where interaction must be one of the basic activities (primitive notions) of the model.…”
Section: Introductionmentioning
confidence: 98%
“…Various flavors of Web service algebras [18], [17], [30], [31], [32] are available in the literature. The RCA differs from these algebras in consideration of recursive composition and its applicability to the well-known problem of Web service interaction verification.…”
Section: Compositionmentioning
confidence: 99%
“…Table 4 presents the time consumption (measured in seconds) in the process of WSCGs generation for the three absolute composition requests shown in Figure 17, 18, and 19. [25][26][27][28][29] We investigated these algebras and found that they are capturing the various composition notions such as sequential, parallel, and choice, but our proposed algebra (RCA) differs from these algebras in the consideration The composition request graph, used in this paper, is inspired from the workflow modeling language Yet Another Workflow Language (YAWL). Based on the data provided in the Table 4 Various flavors of Web service algebras are available in the literature.…”
Section: Scalabilitymentioning
confidence: 99%
“…Various flavors of Web service algebras are available in the literature. () We investigated these algebras and found that they are capturing the various composition notions such as sequential, parallel, and choice, but our proposed algebra (RCA) differs from these algebras in the consideration of recursive composition. Given a service, message, or service‐message tuple, the RCA generates a recursive composition graph automatically, which captures all the possible dependencies among services in order to realize the input.…”
Section: Related Workmentioning
confidence: 99%